The Arab Spring Abroad Diaspora Activism against Authoritarian Regimes - Moss, Dana M. (Social Sciences, 2022)
Diasporas can undermine authoritarian regimes from abroad, but when and how do they become transnational forces for change? By comparing diaspora activism for the Arab Spring revolutions, this book identifies the social forces that make diaspora activism a powerful tool for rebellion and relief.